1989
DOI: 10.1037/0022-3514.56.6.950
|View full text |Cite
|
Sign up to set email alerts
|

Private self-consciousness, self-awareness, and the reliability of self-reports.

Abstract: Two studies found that individuals high in private self-consciousness provide self-reports of greater reliability across time than individuals low in private self-consciousness. In addition, Study 2 found that a successful manipulation of self-awareness did not affect test-retest reliability of self-reports among Ss either high or low in private self-consciousness. The hypothesis that individuals high in private self-consciousness have articulated self-schemata of greater temporal stability than individuals lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…Fenigstein et al suggested that the 23-item scale taps three aspects of self-consciousness: Private Self-Consciousness (PrSC), Public Self-Consciousness, and Social Anxiety. Numerous studies have revealed satisfactory levels of reliability of these three subscales (Fenigstein et al, 1975;Hjelle & Bernard, 1994;McFarland & Sparks, 1985;Nasby, 1989).…”
mentioning
confidence: 99%
“…Fenigstein et al suggested that the 23-item scale taps three aspects of self-consciousness: Private Self-Consciousness (PrSC), Public Self-Consciousness, and Social Anxiety. Numerous studies have revealed satisfactory levels of reliability of these three subscales (Fenigstein et al, 1975;Hjelle & Bernard, 1994;McFarland & Sparks, 1985;Nasby, 1989).…”
mentioning
confidence: 99%
“…And it was Thayer (1971) who made use of this finding to show that those scoring low on a version of the F scale (by implication more self-reflective) were significantly more accurate in their selfratings of physiological changes taking place within themselves. More recently, research with versions of the private self-consciousness measure first constructed by Fenigstein, Scheier, and Buss (1975) has produced similar evidence (e.g., Nasby, 1989) that those who know themselves best (i.e., are most self-aware) make more accurate estimates of their actual behavior than those who know themselves least. Again, when Richardson and McAndrew (1990) used a shortened version of this scale that emphasized internal state awareness (rather than mere self-reflectiveness), they found that more complex imagination images were reported (under conditions of photic stimulation) by those who were most aware of their internal states.…”
Section: Methods Of Investigationmentioning
confidence: 92%
“…In this approach it is assumed that there are people almost permanently focused on themselves by evaluating their own behavior. Such people more accurately assess their characteristics, as shown by the higher correspondence observed in their case between self-description and behavior (Fenigstein, 2009;Nasby, 1989). On the other hand, there are people characterized by very low insight stemming from self-awareness.…”
Section: Self-knowledge and Self-awarenessmentioning
confidence: 98%
“…The ideal self, representing personal hopes and dreams, should lend itself to such self-perception in which, performing a deeper analysis, an individual can see how far he or she is from his or her own ideals. Generating a larger self-discrepancy may stem from better insight in a person exhibiting a higher level of private self-consciousness (Nasby, 1989).…”
Section: Self-consciousness and Self-discrepanciesmentioning
confidence: 99%